Sriwijaya Radio dan Kearifan Lokal melalui Bahasa Daerah Sumatera Selatan - Muhamad Firdaus; Badarudin Azarkasyi (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
This investigation seeks to scrutinize the part played by Sriwijaya Radio in safeguarding indigenous knowledge by utilizing regional languages specific to South Sumatra. With the looming possibility of local languages dying out because Indonesian and foreign languages are so widespread, along with increased urbanization, and shifts in contemporary ways of living, Sriwijaya Radio has become a leading community media outlet that has always used the Palembang language in the programs it broadcasts ever since it was founded on July 13, 2002. A descriptive qualitative method is used in this study, and information is gathered through detailed conversations, observations, and records involving radio managers, broadcasters, program managers, and devoted Sriwijaya Radio listeners at its location on Jalan Seduduk Putih 1, Number 41A, 8 Ilir, Palembang, all of which took place on November 19, 2025. The study's conclusions show that Sriwijaya Radio is very important as a community media platform for protecting regional languages, and it does this through a number of tactics: (1) the consistent use of Palembang language, which includes the unique greeting "Mang Cek & Bik Cek" and the slogan "Sikok-Sikoknyo Radio Palembang," both of which help to create strong emotional connections with listeners; (2) a complete plan for protecting local knowledge through broadcast programs that are based on the cultural values and traditions of Palembang; (3) adapting to digital technology so that it can reach more people without losing its traditional identity; (4) giving the community the power to participate in making content, which results in a preservation environment that can last for a long time. The study's outcomes demonstrate that community-based media outlets, for example, Sriwijaya Radio, serve a significant purpose in revitalizing local dialects. They act not solely as avenues for information and amusement, but also as a means of protecting shared cultural identity during this period of globalization. This investigation enriches the theoretical understanding of community media principles and language conservation. Moreover, it delivers a functional blueprint for similar community media platforms throughout Indonesia as they navigate the difficulties presented by 25 endangered and 11 lost languages, out of the 718 local languages present within the nation.